Ethnobotanical investigation into the Mandi ethnic community in Bangladesh - Partha, Pavel; Hossain, ABM Enayet (Bangladesh Journal of Plant Taxonomy, 2007)
The present ethnobotanical investigation has been carried out into the Mandi ethnic communities of 32 villages of seven upazillas of Dhaka and Sylhet Divisions in Bangladesh. A total of 109 plant species belonging to 59 plant families were found to be used by the communities to treat 38 common human diseases, in ethnoveterinary practices, for pest control, as food, and also to perform rituals, taboos and hunting. Key words: Ethnobotany, Ethnic community, Mandi, Bangladesh DOI: 10.3329/bjpt.v14i2.532 Bangladesh J. Plant Taxon. 14(2): 129-145, 2007 (December)